Anti-hypercholesterolemic Effects and a Good Safety Profile of SCM-198 in Animals: From ApoE Knockout Mice to Rhesus Monkeys - Suguro, Rinkiko; Chen, Siyao; Yang, Di; Yang, Zunyuan; Miao, Lei; Wu, Weijun; Zeng, Wen; Liu, Xinhua; Zhu, Yi Zhun (Frontiers in Pharmacology, 2018)
Although several lipid-lowering agents have been introduced for the treatment of atherosclerosis (AS), currently marketed medications have not solved the problem completely. This study aims to investigate the effects of leonurine (SCM-198) on dyslipidemia in mammals with ApoE knockout (ApoE-/-) mice, New Zealand white rabbits and senile Rhesus monkeys fed with high fat diet were dosed daily with leonurine or atorvastatin. The serum total cholesterol (TC), triglyceride (TG), low density lipoprotein (LDL), and high-density lipoprotein (HDL) were determined. Moreover, in Rhesus monkeys, bodyweight, arterial ultrasound of right common carotid artery, Apolipoprotein A1 (ApoA1) and ApoB levels, hematologic and toxicological examinations were detected. Serum TC and TG in both mice and rabbits were significantly reduced by SCM-198 and atorvastatin. In the 10 mg/kg SCM-198 group of monkeys, maximum TC reduction of 24.05% was achieved at day 150, while 13.16% LDL reduction achieved at day 60, without arterial morphologic changes or adverse events. Atorvastatin (1.2 mg/kg) showed similar effects as SCM-198 in improving lipid profiles in monkeys, yet its long-term use could induce tolerance. Furthermore, leonurine suppressed genes expression of fatty acid synthesis, such as fatty acid synthase (FASN), Stearoyl-CoA desaturase (SCD-1), sterol regulatory element-binding protein (SREBF) in liver in high fat diet feeding ApoE-/- mice. SCM-198, with a reliable safety profile, is of high value in improving lipid profiles in mammals, providing an alternative to a substantial population who are statin-intolerant.